Antiulcerogenic activity and toxicity of bauhinia holophylla hydroalcoholic extract - Rozza, A. L. [UNESP]; Cesar, D. A. S. [UNESP]; Pieroni, L. G. [UNESP]; Saldanha, L. L. [UNESP]; Dokkedal, A. L. [UNESP]; De-Faria, F. M.; Souza-Brito, A. R. M.; Vilegas, Wagner [UNESP]; Takahira, R. K. [UNESP]; Pellizzon, C. H. [UNESP] (Hindawi Publishing Corporation, 2015)
Several species of Bauhinia are used in traditional medicine for the treatment of gastrointestinal diseases, diabetes, and inflammation, among other conditions. The aim of this study was to investigate the antiulcer effect of a hydroalcoholic extract from the leaves of B. holophylla. The chemical profile of the extract was determined by HPLC-PAD-ESI-IT-MS. A dose-effect relation was constructed using the ethanol-induced gastric ulcer model in male Wistar rats. Histological analyses and studies of antioxidant and anti-inflammatory activities were performed in stomach samples. The involvement of SH compounds, NO, K-ATP(+) channels, and alpha(2)-adrenergic receptors in the gastroprotective effect was evaluated. A toxicity study was performed with a single oral dose of 5000 mg/kg. The extract was composed mainly of cyanoglucoside and flavonol-O-glycosides derivatives of quercetin and myricetin. SH compounds, NO release, K-ATP(+) channel activation, and presynaptic alpha(2)-adrenergic receptor stimulation each proved to be involved in the antiulcer effect. The levels of GSH and activity of GR and GPx were increased, and the levels of TNF-alpha, IL-6 and IL-10 were modulated. There was an antidiarrheal effect and there were no signs of toxicity. B. holophylla presents antiulcer activity mainly by decreasing oxidative stress and attenuating the inflammatory response, without inducing side effects.